(untitled) (American Journal of Islam and Society, 2005)
I was persuaded to come out here at rather short notice by the promise of a dialogue on some of the issues professor Bernard Weiss has raised in his conceptually nuanced and politically canny essay on “moderate Islam.”1 In fact, I found it to be such a compelling articulation of key themes that I have focused my own comments around it. (So that we are clear, I am referring to the first draft which has a different slant than the later ones.) My commentary engages the political rather than the theological aspects of the debate on “moderate Islam” and it specifies the problems and the possibilities inherent in two very different approaches to Islam, one that I am calling the official US position and the other simply a Muslim one. I should note that the official perspective also reflects the thinking of most US citizens who support the administration’s policies, so I use the term broadly. In part, this focus reflects my disciplinary bias. As someone who comes to the study of religion through the conceptual lens of politics, I am very mindful of the relationship between structures of power and the interpretation and practice of religion both in states where religion and politics intersect in obvious ways and in those that are designed to sustain the separation of church and state. In actuality, of course, religion and politics are inseparable even in secular states though this does not mean that they are therefore simply reducible to one another even in states where they exist in open symbiosis. I make this point because of the tendency to represent Muslim identity as irreducibly religious, as if we cannot have a will, desire, agency, consciousness, or purpose that are fundamentally political just because we look to religion to lend meaning to our lives. I want, therefore, to recuperate some sense of Muslim political identity in my talk ...